2022
DOI: 10.21037/atm-21-6347
|View full text |Cite
|
Sign up to set email alerts
|

A validated nomogram integrating baseline peripheral T-lymphocyte subsets and NK cells for predicting survival in stage I–IIIA non-small cell lung cancer after resection

Abstract: Background: Accurately predicting the risk of recurrence in stage I-IIIA non-small cell lung cancer (NSCLC) after resection is critical in the treatment process. This study aimed to establish a novel nomogram to identify patients with a risk of disease progression in stage I-IIIA lung cancer based on clinical characteristics, peripheral T-lymphocyte subsets, and CD16+56 natural killer (NK) cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Similar to neoadjuvant therapy, neoadjuvant immunotherapy aims to shrink the primary tumor and enable downstaging, thereby facilitating or simplifying surgery ( 32 ). Despite the variety of clinical prognostic prediction models for neoadjuvant therapy, T staging is commonly included and recognized as a critical predictor of patient outcomes ( 33 , 34 ), aligning with the findings of our model.…”
Section: Discussionsupporting
confidence: 73%
“…Similar to neoadjuvant therapy, neoadjuvant immunotherapy aims to shrink the primary tumor and enable downstaging, thereby facilitating or simplifying surgery ( 32 ). Despite the variety of clinical prognostic prediction models for neoadjuvant therapy, T staging is commonly included and recognized as a critical predictor of patient outcomes ( 33 , 34 ), aligning with the findings of our model.…”
Section: Discussionsupporting
confidence: 73%
“…Nomograms, a statistic-based tool, can assess the risk of clinicopathological features by quantifying the biological and clinical variables of patients with cancer (6). To date, nomograms have been widely applied in the personalized prediction of cancer, such lung, cervical, prostate, and hepatocellular carcinomas (7)(8)(9)(10)(11). To the best of our knowledge, several studies have reported risk factors associated with breast cancer (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…11 In lung cancer patients, peripheral CD8+ T-cell counts were higher than in healthy controls, but CD3+, CD4+ T cells, and the CD4+/CD8+ were considerably lower. 12 Additionally, individuals with lung cancer who had higher percentages of peripheral CD3+ and CD4+ T cells, and higher CD4/CD8 ratios, had longer overall survival times. 13 Podoplanin (PDPN) is a mucin-type transmembrane glycoprotein that is known to be a hallmark of lymphatic endothelial cells.…”
Section: Introductionmentioning
confidence: 98%